Prenatal and pubertal exposure to 17α-ethinylestradiol cause morphological changes in the prostate of old gerbils - Fleury, Fernanda G.; Guimarães, Luísa R. F.; Rezende, Elisa B.; Martins, Tracy M. M.; Caires, Cássia R. S.; dos Santos, Fernanda C. A.; Taboga, Sebastião R. [UNESP]; Perez, Ana P. da S. (Wiley, 2021)
This study evaluated such as exposure to ethinylestradiol during the prenatal (18th–22nd day) and pubertal (42nd–49th day) periods acts on the male ventral prostate and female prostate of 12-month old gerbils. We performed the analysis to serum hormone levels for estradiol and testosterone. The prostates were submitted to morphometric and immunohistochemical analyses. Exposure to ethinylestradiol during these developmental periods decreased the testosterone serum levels in males and increased the estradiol serum levels in females. Morphologically, prostate intraepithelial neoplasia and disorders in the arrangement of the fibrous components were observed in the prostate glands of both sexes of gerbil exposed to ethinylestradiol during development periods. In the male prostate, the ethinylestradiol promoted decreased in the frequency of positive epithelial cell for androgen receptor (AR) and increased the frequency of positive stromal cell for estrogen receptor α. However, in the female prostate, this synthetic estrogen caused AR upregulation and increased cell proliferation. This study shows that the exposure to ethinylestradiol during development phases alters the morphology and the hormonal signaling in the male and female prostates of old gerbils, confirming the action of ethinylestradiol as endocrine disruptor.
Keywords: development; female; male; oral contraceptive; prostate